A rare case of chronic suppurative otitis media with foreign body in external auditory canal and mastoid antrum - Simha, Vijayendra; M, Suma (International Journal of Research in Medical Sciences, 2017)
Foreign bodies in External Auditory Canal (EAC) are common in both adults and children. Removal of foreign body requires skill but usually successfully performed in the ENT department. A 40 year old female patient presented with right ear discharge with decreased hearing. On examination, a pale, scanty, mucopurulent discharge, foul smelling with blood tinge, persisting even after medications. After aural toileting, tympanic membrane was perforated with granulation tissue in middle ear. Multiple broom sticks were found in the external auditory canal, mastoid antrum was removed via post auricular approach with excision of polyp with radical mastoid exploration. Removal of foreign body from EAC is an essential skill for ENT surgeon. Careful removal can prevent further trauma and complications. An aural polyp with ear discharge, never attempt to pull/avulsion.